(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
Molecular markers have emerged as indispensable tools in onion improvement, facilitating precise assessment of genetic diversity, trait mapping, and marker-assisted selection. Their application has accelerated the development of cultivars with desirable characteristics, including enhanced bulb quality, disease resistance, and stress tolerance. Molecular breeding has revolutionized onion improvement by providing reliable, environment-independent methods for germplasm characterization, genetic diversity analysis, and the construction of high-density genetic maps for gene tagging and selection. These markers are extensively employed in DNA fingerprinting for varietal identification, breeding line validation, and plant variety protection. They also play a crucial role in identifying and transferring resistance genes against biotic and abiotic stresses. Onion breeding has particularly benefited from marker-assisted improvement of traits such as male sterility, earliness, bulb color, yield, total soluble solids, and bolting resistance. Recent advancements have enabled the mapping of genes controlling bulbing and flowering, as well as loci associated with disease resistance and hybrid development. Overall, molecular marker technologies have greatly enhanced the efficiency of onion breeding, supporting the rapid development of elite, high-performing cultivars.